Blood biomarkers for the diagnosis and differentiation of stroke: A systematic review and meta-analysis. Issue 7 (October 2020) - Misra, Shubham; Montaner, Joan; Ramiro, Laura; Arora, Rohan; Talwar, Pumanshi; Nath, Manabesh; Kumar, Amit; Kumar, Pradeep; Pandit, Awadh K; Mohania, Dheeraj; Prasad, Kameshwar; Vibha, Deepti
Background: Correct diagnosis of stroke and its subtypes is pivotal in early stages for optimum treatment. Aims: The aim of this systematic review and meta-analysis is to summarize the published evidence on the potential of blood biomarkers in the diagnosis and differentiation of stroke subtypes. Methods: A literature search was conducted for papers published until 20 April 2020 in PubMed, EMBASE, Cochrane Library, TRIP, and Google Scholar databases to search for eligible studies investigating the role of blood biomarkers in diagnosing stroke. Quality assessment was done using modified Quality Assessment of Diagnostic Accuracy Studies questionnaire. Pooled standardized mean difference and 95% confidence intervals were calculated. Presence of heterogeneity among the included studies was investigated using the Cochran's Q statistic and I 2 metric tests. If I 2 was < 50% then a fixed-effect model was applied else a random-effect model was applied. Risk of bias was assessed using funnel plots and between-study heterogeneity was assessed using meta-regression and sensitivity analyses. Entire statistical analysis was conducted in STATA version 13.0. Results: A total of 40 studies including patients with 5001 ischemic strokes, 756 intracerebral hemorrhage, 554 stroke mimics, and 1774 healthy control subjects analyzing 25 biomarkers (within 24 h after symptoms onset/after the event) were included in our meta-analysis; 67.5% of studies had moderate evidence of quality. Brain natriuretic peptide, matrix metalloproteinase-9, and D-dimer significantly differentiated ischemic stroke from intracerebral hemorrhage, stroke mimics, and health control subjects ( p  < 0.05). Glial fibrillary acidic protein successfully differentiated ischemic stroke from intracerebral hemorrhage (standardized mean difference −1.04; 95% confidence interval −1.46 to −0.63) within 6 h. No studies were found to conduct a meta-analysis of blood biomarkers differentiating transient ischemic attack from healthy controls and stroke mimics. Conclusion: This meta-analysis highlights the potential of brain natriuretic peptide, matrix metalloproteinase-9, D-dimer, and glial fibrillary acidic protein as diagnostic biomarkers for stroke within 24 h. Results of our meta-analysis might serve as a platform for conducting further targeted proteomics studies and phase-III clinical trials. PROSPERO Registration ID: CRD42019139659.